Extraction bag lavage cytology during video-assisted thoracoscopic surgery for primary lung cancer. (26th February 2014) - Nakano, Tomoyuki; Tetsuka, Kenji; Endo, Tetsuya; Kanai, Yoshihiko; Otani, Shinichi; Tsubochi, Hiroyoshi; Yamamoto, Shinichi; Endo, Shunsuke
Abstract: OBJECTIVES: Sample extraction from the thoracic cavity through an intercostal space during video-assisted thoracoscopic surgery can result in cancer cell contamination by tumour crushing and tumour cell extravasation, and may have adverse effects on the surgical outcome. Lavage cytology of the sample extraction bag was investigated to clarify the risk of cancer cell spillage and identify the clinicopathological features associated with susceptibility to cancer cell spillage during extraction. METHODS: Lavage cytology of the sample extraction bag was investigated in 464 patients with negative pleural lavage cytology who underwent lung resection for primary lung cancer via video-assisted thoracoscopic surgery between January 2010 and December 2012. The surgical procedures, pathological findings and clinical course were evaluated by hospital record review. RESULTS: The incidence of positive bag lavage cytology (BLC) was 13.6%. Statistically significant factors associated with susceptibility to BLC positivity were tumour size, standardized uptake value of positron emission tomography, pathological features such as pathological N score, pleural invasion, vascular invasion and papillary-predominant adenocarcinoma. Among patients with Stage I lung cancer, the survival rate was significantly lower in the BLC-positive group than in the BLC-negative group. CONCLUSIONS: BLC positivity can be related to oncological characteristics such as tumour invasiveness and adhesiveness as opposed to tumour size and surgical margin, and may help to determine the prognosis of Stage I lung cancer. The sample extraction bag must be carefully manoeuvred through the intercostal space to prevent cancer cell dissemination to the chest wall or thoracic cavity.